2012
DOI: 10.1007/978-3-642-25755-1_11
|View full text |Cite
|
Sign up to set email alerts
|

An Agent-Based Modeling for Pandemic Influenza in Egypt

Abstract: Pandemic influenza has great potential to cause large and rapid increases in deaths and serious illness. The objective of this paper is to develop an agent-based model to simulate the spread of pandemic influenza (novel H1N1) in Egypt. The proposed multi-agent model is based on the modeling of individuals' interactions in a spacetime context. The proposed model involves different types of parameters such as: social agent attributes, distribution of Egypt population, and patterns of agents' interactions. Analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 11 publications
0
37
0
3
Order By: Relevance
“…Even in these approaches the mobility pattern of human or spatio-temporal aspect is not discussed. SIR model is based on Agent Based Modeling (ABM) [14] to model the infectious individual interactions based on space, time, age and population structure. The ability to model the spread of disease is a critical issue for governments and health organizations.…”
Section: Related Workmentioning
confidence: 99%
“…Even in these approaches the mobility pattern of human or spatio-temporal aspect is not discussed. SIR model is based on Agent Based Modeling (ABM) [14] to model the infectious individual interactions based on space, time, age and population structure. The ability to model the spread of disease is a critical issue for governments and health organizations.…”
Section: Related Workmentioning
confidence: 99%
“…; or (b) testing the consequences of alternative actions, when these alternatives exist in reality and the best choice is not clear, e.g. [Khalil et al 2010].…”
Section: Usagementioning
confidence: 99%
“…Nevertheless, Egypt had the highest number of human fatalities in Africa as a result of the swine flu pandemic. Therefore it is unsurprising that the first application of an ABS developed at Cairo University, dubbed IMAMCR (Intelligent Multi-Agent Model for Crisis Response) in [Khalil et al 2009], was to determine the optimal response to a flu pandemic in Egypt [Khalil et al 2010]. IMAMCR is another example of optimizing existing resources and procedures.…”
Section: Abs For Large-scale Emergency Responsementioning
confidence: 99%
“…Kim et al [29] demonstrated the use of Agent based Model to demonstrate it can be used to estimate and predict the spread of Avian Influenza (AI) in various attributes and environments in a given population (South Korea) and to aid in the identify an effective means to contain the flu. Khalil et al [30] is another example illustrated the use of Agent-based Model to identify optimal containment strategies for a Pandemic in Egypt. Nevertheless, to the knowledge of the authors, there has been no attempt on the modelling of containment of Malware by incident responders.…”
Section: Agent Based Modellingmentioning
confidence: 99%
“…Chen et al [32] did the same for the simulation of smallpox outbreak. Khalil et al [30]'s paper on Agent-based Modelling of Pandemic used the same approach. Skvortsov et al [33] argued that aligning the inputs and outputs of both Agent Based Model and SIR model provides a necessary foundational validation step so that the ABM can be extended to handle more complex scenarios which is the intent of this research.…”
Section: B Evaluation Approachmentioning
confidence: 99%